Surgical treatment of esophagogastric varices from cavernous transformation of portal vein: one case report - SUN Longci, ZHANG Bin (Waike lilun yu shijian, 2021)
Objective To discuss the treatment of esophagogastric varices fom cavernous transformation of portal vein(CTPV). Methods A 2l-year-old male patient with CTPV from Department of Gastrointestinal Surgery Renji Hospital im2020 was analyzed retrospectively. Results The patient was admitted with lower WBC count 1.38×109/L and lower plateletcount 37×109/L and abdominal enhanced CT scan showedl main portal vein obliteration and collateral vessels proximal tothe obstruction.The examination revealed negative hepatitis markers and Child-Pugh A stage.He was diagnosed as CTPvassociated with large esophagogastric varices, massive splenomegaly and hypersplenism. He underwent splenectomy,splenorenal shunting and pericardial devascularization and the postoperative recovery was uneventful without hepaticencephalopathy. Postoperative abdominal CTA was suggestive of splenorenal shunt patent. Conclusion lt was suggested that preventive shunting and devascularization were suitable for CTPV associated with large esopha gogastric varices, massive splenomegaly and hypersplenism.